Obstetric risk and neonatal health in times of Sars-CoV-2 (Covid-19) pandemic in a public hospital in Peru (GnosisWisdom, 2023)
Objective. To characterize the obstetric and neonatal clinical behavior during the Sars-CoV-2 (Covid-19) pandemic in a Peruvian public hospital.Materials and Methods. Type of study was descriptive, descriptive level, non-experimental design, descriptive transactional, scientific method and documentary analysis. The population and sample consisted of pregnant women and newborns. The documentary analysis technique was used, as well as the documentary content analysis form.Results. 40.8% of pregnant women with Sars-CoV-2 (Covid-19) infection had a euthyroid delivery and 57.1% of gestations without infection had a dystocic delivery; 33.3% with infection had a dystocic delivery; there was a significant difference in the type of delivery (pvalue= ,000). 48.3% and 40.1% of pregnant women with and without infection were primiparous; there was no difference for the type of parity presented by the pregnant women (pvalue= ,509). 33.3% and 38.5% with and without Sars-CoV-2 (Covid-19) infection were primigravid; there was no difference in the type of gestation they presented (pvalue= ,550). 78.3% and 64.35 of neonates evaluated from pregnant women with and without Sars-CoV-2 (Covid-19) infection reached scores of 8 per minute in Appearance (skin color), Pulse (heart rate), Gesticulation (gestures; response to stimuli), Activity (muscle tone), and Respiration (APGAR), with no difference (pvalue= ,169); the great majority of newborns reached a level of tolerance to the birth process and its possible suffering. The 90.8% and 83.0% of neonates reached a score of 9 at 5 minutes; there was no difference if their mothers were infected by Sars-coV-2 (Covid-19) (pvalue= ,277); indicating that the newborns reached a level of adaptability to the environment and their ability to recover.Regarding hospital stay, 55.8% of neonates were hospitalized for 2 days, while 60.4% of neonates of mothers without infection were hospitalized for 5 days, with a significant difference (pvalue= ,000). And in reference to the time for umbilical cord ligation, 95.0% of the neonates evaluated from pregnant women with Covid-19 infection were exposed to ligation within one minute; but in neonates from mothers without infection, 100.0% were exposed to ligation within three minutes; there was a significant difference (pvalue= ,000).Conclusions. Pregnant women and neonates who were attended in times of pandemic presented complications at the time of delivery and in the adaptation to extrauterine life.
Keywords: Obstetric risk; neonatal health; newborn; gestation; Covid-19